A review of interventions against fetal alcohol spectrum disorder targeting oxidative stress. Issue 71 (December 2018) - Zhang, Yuanpei; Wang, Hongxuan; Li, Yi; Peng, Ying
Highlights: Oxidative stress is associated with Fetal alcohol spectrum disorders (FASDs). Studies have shown a number of interventions against FASDs through preventing or ameliorating oxidative stress. Most interventions up to now are assayed only in animal models. Abstract: Introduction: Fetal alcohol spectrum disorder is caused by maternal ethanol exposure; it causes physical, behavioral, cognitive, and neural impairments (Murawski et al., 2015). Mechanisms of FASD causing damage are not yet fully elucidated. Oxidative stress might be one of its mechanisms (Henderson et al., 1995). Yet no effective treatment against FASD has been found other than ethanol abstention (Long et al., 2010). Methods: This review summarizes relevant literatures regarding interventions targeting oxidative stress that may relieve fetal alcohol spectrum disorder. Results: Astaxanthin was found to mitigate embryonic growth retardation induced by prenatal ethanol treatment through ameliorating the down regulation of hydrogen peroxide (H2O2) and malondialdehyde (MDA) caused by alcohol in a mice model (Zheng et al., 2014; Vabulas et al., 2002). Vitamin E protected against fatal alchol spectrum disorders by ameliorating oxidative stress in rat models (Mitchell et al., 1999a), and yielded a better outcome when it was combined with Vitamin C (Packer et al., 1979; Peng et al., 2005). Vitamin C mitigated embryonic retardation caused by alcohol and reversed ethanol induced NF-κB activation and ROS (reactive oxygen species) formation in a Xenopus laevis model (Peng et al., 2005). Beta carotene supplement was proved to protect against neurotoxicity in hippocampal cultures of embryos induced by alcohol in a rats model (Mitchell et al., 1999a). Prenatal folic acid supplement reversed the decrease of body weight caused by maternal ethanol treatment and ameliorated the increment of glutathione reductase specific activities as well as the increase of thiobarbituric acid reactive substances (TBARS) induced by alcohol in a rats model (Cano et al., 2001). Omega-3 fatty acids reversed the decrease of reduced glutathione (GSH) levels in brain caused by prenatal ethanol treatment in a rats model (Patten et al., 2013). EUK-134 treatment reduced the incidence of forelimb defects caused by ethanol treatment in a mice model (Chen et al., 2004). Pretreatment of activity-dependent neurotrophic factor-9 (ADNF-9) and NAPVSIPQ (NAP) protected against prenatal ethanol induced fetal death as well as fetal growth abnormalities in a mice model, and such treatment reversed the decrease of the rate of reduced glutathione (GSH)/ oxidative glutathione (GSSG) caused by alcohol (Spong et al., 2001). Conclusion: By now interventions against fetal alcohol spectrum disorder targeting oxidative stress includes astaxanthin, Ascorbic acid (Vitamin C), Vitamin E, beta-carotene, (–)-Epigallocatechin-3-gallate (EGCG), Omega-3 fatty acids, etc (see Fig. 1). However, most interventions are only assayed in animal models, more clinical trials are needed to show whether antioxidants make an effort against FASD damage.